If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = -4(-7x + -3) Reorder the terms: 12 = -4(-3 + -7x) 12 = (-3 * -4 + -7x * -4) 12 = (12 + 28x) Add '-12' to each side of the equation. 12 + -12 = 12 + -12 + 28x Combine like terms: 12 + -12 = 0 0 = 12 + -12 + 28x Combine like terms: 12 + -12 = 0 0 = 0 + 28x 0 = 28x Solving 0 = 28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28x' to each side of the equation. 0 + -28x = 28x + -28x Remove the zero: -28x = 28x + -28x Combine like terms: 28x + -28x = 0 -28x = 0 Divide each side by '-28'. x = 0 Simplifying x = 0
| w^2+7w-9=0 | | n-.6n+20000=.15n | | 5xy^5= | | t^2-2t=7 | | w^2=3w+54 | | 400=4t^2+18t | | .50a-3=7-.75a | | 3+4x=3x-7 | | 2(4x+9)=-78 | | (x-2)2+x(x-3)=3(x+4)(x-3)-(x+2)(x-1)+2 | | 3a^3-4a=0 | | 9c^2+6c=0 | | .66x+5=.33x+14 | | 3(8-7x)=-207 | | 4a^3-a=0 | | -5(2x+1)=-45 | | 2(2+5x)=-66 | | 4(2z-2)=7(z-4) | | (8x^3-7x^2+10x-9)-(2x^3-5x^2-8x+9)= | | 13=x+18 | | x^5(2-x)=0.98 | | 6(10+2x)=60 | | 30d^2+37d+10=0 | | -3(-7x+6)=-270 | | 7(3x-7)=-70 | | 7(-6x+4)=-434 | | 7x+5y=10000 | | 9+4m=2m-15 | | 9(4m)=2m-15 | | x=51/3+87/12 | | a^2-a^4=0 | | 0.5-x=0.28x |